Novel genetic variants associated with lumbar disc degeneration in northern Europeans: a meta-analysis of 4600 subjects. Issue 7 (19th September 2012) - Williams, Frances M K; Bansal, Aruna T; van Meurs, Joyce B; Bell, Jordana T; Meulenbelt, Ingrid; Suri, Pradeep; Rivadeneira, Fernando; Sambrook, Philip N; Hofman, Albert; Bierma-Zeinstra, Sita; Menni, Cristina; Kloppenburg, Margreet; et al.
Abstract : Objective: Lumbar disc degeneration (LDD) is an important cause of low back pain, which is a common and costly problem. LDD is characterised by disc space narrowing and osteophyte growth at the circumference of the disc. To date, the agnostic search of the genome by genome-wide association (GWA) to identify common variants associated with LDD has not been fruitful. This study is the first GWA meta-analysis of LDD. Methods: We have developed a continuous trait based on disc space narrowing and osteophytes growth which is measurable on all forms of imaging (plain radiograph, CT scan and MRI) and performed a meta-analysis of five cohorts of Northern European extraction each having GWA data imputed to HapMap V.2. Results: This study of 4600 individuals identified four single nucleotide polymorphisms with p<5×10 −8, the threshold set for genome-wide significance. We identified a variant in the PARK2 gene (p=2.8×10 −8 ) associated with LDD. Differential methylation at one CpG island of the PARK2 promoter was observed in a small subset of subjects (β=8.74×10 −4, p=0.006). Conclusions: LDD accounts for a considerable proportion of low back pain and the pathogenesis of LDD is poorly understood. This work provides evidence of association of the PARK2 gene and suggests that methylation of the PARK2 promoter may influence degeneration of the intervertebral disc. This gene has not previously been considered a candidate in LDD and further functional work is needed on this hitherto unsuspected pathway.